Adsorption and reduction of Cr(VI) from aqueous solution using cost-effective caffeic acid functionalized corn starch. (September 2021) - Liu, Fenglei; Hua, Shan; Wang, Chao; Qiu, Muqing; Jin, Limin; Hu, Baowei
Abstract: Herein, a potential bio-adsorbent (DACS-CA) was formed via immobilizing caffeic acid (CA) on dialdehyde corn starch (DACS) for Cr(VI) removal. The characterization techniques such as IR, Raman, XPS and 13 C NMR were performed to analyze surface elements and functional groups on the as-prepared sorbents. Batch experiments revealed that the maximum Cr(VI) removal amount (96.45 mg/g) took place at a pH value of 3.0, adsorption temperatures of 333 K and solid-liquid ratio of 0.2. The isotherms studies found that the Cr(VI) removal of DACS-CA was monolayer adsorption, while the kinetics analysis revealed that chemisorption was the main power for removal process. Characterization analysis found that about Cr(VI) (53.02%) and Cr(III) (46.98%) species co-existed onto the surface of DACS-CA, which implied that a redox reaction may be occurred between Cr(VI) and the bio-adsorbent. Namely, Cr(VI) was first loaded on DACS-CA via electrostatic interaction, subsequently Cr(VI) was partially transformed into Cr(III) by reductive functional groups, meanwhile the resulting Cr(III) was immobilized by the carboxyl groups of DACS-CA. Thus, this bio-adsorbent could serve as an efficient sorbent for the removal of Cr(VI) from wastewater in environmental pollution cleanup. Graphical abstract: Image 1 Highlights: An efficient bio-adsorbent (DACS-CA) was successfully prepared. DACS-CA exhibited an excellent removal performance towards Cr(VI). The adsorption conditions played an important role in Cr(VI) removal. Removal of Cr(VI) was proved to be an adsorption-reduction process.